The impact of war: New business networks and small-scale contractors in Britain, 1739–1770. Issue 1 (2nd January 2018) - Bannerman, Gordon
Abstract: This article argues that the resources and skills of military contractors were a crucial component of the war-making capacity of the British state in the mid-eighteenth century. Contractors used product knowledge, access to capital and credit, market intelligence, and personal and professional connections to perform contracts effectively, and by doing so contributed towards operational capability and combat readiness. Contracting not only reveals the diversity of the domestic economy but also the degree of connectivity between different sectors. Problems of scale, cost, and risk were overcome by harnessing and channelling broad expertise across different sectors. If modern states were highly innovative in fiscal-military terms, contractors were no less so in managing extensive supply operations.